Necessity and Importance of Investments in the Country’s Economy - Shayakubov Shakhzod Shakabilovich (Global Scientific Publishing, 2023)
In today’s era of globalization and fierce competition, it is difficult to imagine the sustainable development of the country’s economy without its active participation in world economic relations. Along with international trade, international investment flows based on mutually beneficial cooperation between the two countries are of great importance today. In turn, foreign investment will accelerate the pace of structural restructuring of the economies of developing countries. Attracting foreign investment as the most important direction will largely depend on the ongoing political and socio-economic reforms in a country. Foreign investment plays an important role at both the macro and micro levels, it determines the future of the individual business entity and the country as a whole, and is the driving force of the economy.
Keywords: innovative activity; innovative product; investment